Gene Conversion-Like Events in the Diversification of Human Rearranged IGHV3-23*01 Gene Sequences - Duvvuri, Bhargavi; Wu, Gillian E. (Frontiers in Immunology, 2012)
Gene conversion (GCV) as a mechanism of immunoglobulin diversification is well established in a few species. However, definitive evidence of GCV-like events in human immunoglobulin genes is scarce. GCV is mediated by activation-induced cytidine deaminase (AID). The lack of evidence of GCV in human rearranged immunoglobulin gene sequences is puzzling given the presence of highly similar germline donors and all the enzymatic machinery required for GCV. In this study, we undertook a computational analysis of rearranged IGHV3-23*01 gene sequences from common variable immunodeficiency (CVID) patients and healthy individuals to survey ‘GCV-like’ activities. Our search identified strong evidence of GCV-like patterns. Germline VH sequences were identified as potential donors for clustered mutations in rearranged IGHV3-23*01 gene sequences. We identified minimum and maximum sequence identities between donor and recipient sequences that can serve as targets for GCV and our findings are consistent with those reported in literature. We observed that GCV-like tracts are flanked by activation-induced cytidine deaminase (AID) hotspot motifs. Structural modeling of IGHV3-23*01 gene sequence revealed that hypermutable bases flanking GCV-like tracts, are in the single stranded DNA (ssDNA) of stable stem-loop structures (SLSs). SsDNA is inherently fragile and also an optimal target for AID. We speculate that GCV could have been initiated by the targeting of hypermutable bases in ssDNA state in stable SLSs, plausibly by AID. We have observed that the frequency of GCV-like events is significantly higher in rearranged IGHV323-*01 sequences from healthy individuals compared to that of CVID patients. GCV, unlike SHM, can result in multiple base substitutions that can alter many amino acids. The extensive changes in antibody affinity by GCV-like events, as identified in this study would be instrumental in protecting humans against pathogens that diversify their genome by antigenic shift.